The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12991-022-00413-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative syndrome scale in forensic patients with schizophrenia spectrum disorders: a systematic review and meta-analysis

Abstract: Among forensic patients with schizophrenia spectrum disorders, the association between symptomatology and violence is still not entirely clear in literature, especially because symptoms shift both during the acute phase of the illness and after. The aims were to investigate the level of symptomatology in forensic patients and to evaluate if there are differences in the level of symptoms between forensic and non-forensic patients. According to PRISMA guidelines, a systematic search was performed in PubMed, Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…Among them, schizophrenia and bipolar disorder are the most prevalent, affecting around 24 and 40 million people worldwide over the last decade, respectively [ 1 , 2 , 3 , 4 , 5 ]. Schizophrenia is a chronic disorder, most commonly beginning in late adolescence and early adulthood, characterized by the presence of positive symptoms, such as hallucinations, delusions and significant and intense changes in thought and behavior (such as self or hetero-aggressiveness, agitation and bizarre attitudes), negative symptoms, such as dementia, impairment of interpersonal relationships, social isolation, apathy, alogia, anhedonia and lack of motivation and initiative to perform ordinary everyday activities, and cognitive symptoms, such as marked deficits in verbal and working memory, vigilance and attention [ 6 , 7 , 8 , 9 , 10 ]. In turn, bipolar disorder is also a chronic mental illness, typically characterized by either recurrent depressive episodes, including feelings of deep sadness and energy loss, or episodes of mania/hypomania, including periods during which people feel overly exhilarated, happy, irritable and/or energetic, with a reduced need to sleep [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, schizophrenia and bipolar disorder are the most prevalent, affecting around 24 and 40 million people worldwide over the last decade, respectively [ 1 , 2 , 3 , 4 , 5 ]. Schizophrenia is a chronic disorder, most commonly beginning in late adolescence and early adulthood, characterized by the presence of positive symptoms, such as hallucinations, delusions and significant and intense changes in thought and behavior (such as self or hetero-aggressiveness, agitation and bizarre attitudes), negative symptoms, such as dementia, impairment of interpersonal relationships, social isolation, apathy, alogia, anhedonia and lack of motivation and initiative to perform ordinary everyday activities, and cognitive symptoms, such as marked deficits in verbal and working memory, vigilance and attention [ 6 , 7 , 8 , 9 , 10 ]. In turn, bipolar disorder is also a chronic mental illness, typically characterized by either recurrent depressive episodes, including feelings of deep sadness and energy loss, or episodes of mania/hypomania, including periods during which people feel overly exhilarated, happy, irritable and/or energetic, with a reduced need to sleep [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that while patients with SCH are more likely to engage in violent behaviors (8), only a fraction of violent offenders have SCH (9,10). As a result of psychotic symptoms, SCH patients frequently exhibit aggressivity (11)(12)(13), especially during an acute episode (14,15). Previous studies have demonstrated that patients with psychopathological conditions were more prone to engage in aggressive actions when suffering from auditory hallucinations, particularly command hallucinations (16,17).…”
Section: Introductionmentioning
confidence: 99%